The good and the bad of remote work: A JDR-Model overview about the impact of remote work on university professors - Gomes, Ian Pedro de Sousa Pugsley (2021)
Covid-19 has abruptly changed the way organizations work and universities have not been left out as faculty members have been forced to adopt remote working as their newborn baby. This research examines, according to the JDR-model, what are the demands and resources that colleges of higher education have at their disposal during remote working. With this aim, a study was carried out with a sample of Portuguese universities, at two different moments. At the first moment the sample consisted of 126 individuals. The second moment consisted of data collection in three different weeks, where in the first week we obtained 125 answers, 62 answers regarding the second week and 53 answers regarding the third week. In the first moment, the perceived family support and the impact of remote work were assessed, in particular on technostress, work-family conflict, and the absence of social interaction. The results showed that work-family conflict and the absence of social interaction mediate the relationship between family support and technostress. Moreover, engagement, performance and positive affect were also tested during the second moment, during three different weeks. The results revealed that engagement is positively associated with performance. Additionally, positive affect moderates the relationship between engagement and performance. The practical and theoretical implications of the results were also analyzed, followed by potential questions for future research, with suggestions for improvement.